A escola primária noturna na política educacional mineira 1981-1924 - Vera Lucia Nogueira (2009)
This work aims to analyze the configuration of the educational policy in the state of Minas Gerais for diligent population young adult in the period between 1891 and 1924. It also aims to understand the consequences of the educational reforms in defining and organizing the evening primary school developed by this State, municipalities, by private schools and workers associations. Some ideas and concepts developed by authors like Roger Chartier, Norberto Bobbio, E. P. Thompson, René Rémond, Viñao Frago, Faria Filho, among others, have contributed to the dialogue with document sources. The main sources analyzed were the annals of the Minas Gerais Congress, the educational legislations, the technical inspection terms for teaching, and several board of directors reports, several mails received and sent by the Department of the Interior, reports from the Secretaries of the Interior and of Justice, messages from the State Presidents, among others. In addition to those sources, newspapers from that time were also used, such as Minas Gerais, the state official journal, O Operário from the Workers League, O Labor, the diffusion organism from the Workers Auxiliary Confederation of Minas Gerais, and O Confederal, from the State Confederative Center. It was possible to observe that the educational policy to serve workers from Minas Gerais was established pari passu with the building of the Educational Policies for Children from Minas Gerais, and that the policy beneficiaries only began to be differentiated in a progressive way from the third republican decade on, mainly by defining the scholar age and the specific teaching programs for evening schools. Besides that, it can be stated that concerns about the primary education of workers have gained space in the political agenda of the workers movement in Minas Gerais and have been transformed into concrete initiatives especially turned to workers with ages above the day-school age. The intergenerational contact may, however, be considered one of the characteristics of the evening primary-school teaching in Minas Gerais, as well as the ambiguity when programs are elaborated and the childish teaching instructions destined to adult individuals attending evening classes. It can also be highlighted, among other factors that the educational services policy to workers of Minas Gerais counts on a chain of institutions connected with a common goal of educating, bringing light to the shameful poverty of this State.